2008
DOI: 10.4070/kcj.2008.38.9.441
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effects of Cilostazol on Atherosclerotic Vascular Disease

Abstract: Cilostazol inhibits phosphodiesterase III (PDE III), which is predominantly distributed to and regulates physiologic responses in platelets, cardiac muscle cells, vascular smooth muscle cells, and adipose cells. Clinically, it is well known as an antiplatelet agent that inhibits the platelet aggregation normally induced by collagen, 5'-adenosine diphosphase (ADP), epinephrine, and arachidonic acid. It also has pleotropic effects, including the prevention of restenosis after angioplasty and the promotion of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…These findings might be because the VerifyNow Aspirin system is not adequate to assess the antiplatelet activity of cilostazol. Cilostazol act upstream of COX-1 pathway by suppressing the release of arachidonic acid in platelets, therefore direct arachidonic acid stimulation of the VerifyNow Aspirin system may bypass the action of cilostazol [ 21 , 22 ]. Several previous studies also failed to identify antiplatelet activity of cilostazol with the VerifyNow Aspirin system.…”
Section: Discussionmentioning
confidence: 99%
“…These findings might be because the VerifyNow Aspirin system is not adequate to assess the antiplatelet activity of cilostazol. Cilostazol act upstream of COX-1 pathway by suppressing the release of arachidonic acid in platelets, therefore direct arachidonic acid stimulation of the VerifyNow Aspirin system may bypass the action of cilostazol [ 21 , 22 ]. Several previous studies also failed to identify antiplatelet activity of cilostazol with the VerifyNow Aspirin system.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale clinical studies did not show differences for the two therapies in the incidence of complications such as bleeding or gastrointestinal complications 13)21)22). The lack of established criteria for treatment periods for anti-platelet agents implies the need for individual treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale clinical studies did not show differences for the two therapies in the incidence of complications such as bleeding or gastrointestinal complications. 13) 21) 22) The lack of established criteria for treatment periods for anti-platelet agents implies the need for individual treatment plans. The results of this study suggests that triple therapy may be useful in type 2 diabetic patients with left main coronary artery lesion, bifurcation lesions, or long lesions with high risk of stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we have tried to find appropriate plasma atherosclerotic biomarkers in T2DM patients with ASO to evaluate the effectiveness of Cilostazol and Probucol, along with their combination, because these drugs have anti-oxidative activities [3],[17]. The previous in vitro study with cultured human coronary artery endothelial cells,[23] in vivo studies in rats and in LDL receptor-deficient mice revealed the synergetic effect of Cilostazol plus Probucol against oxidative stress and atherosclerotic lesions [24],[25].…”
Section: Introductionmentioning
confidence: 99%
“…Cilostazol also has pleiotropic effects against oxidative stress on vascular function and atherosclerosis. [17] …”
Section: Introductionmentioning
confidence: 99%